Morphological and optical properties of graphene film synthesized from waste of industrial cooking oil, AYAMAS using dtcvd method / Nurfazianawatie Mohd Zin … [et al.] - Mohd Zin, Nurfazianawatie; Abdullah, Nurul Afaah; Mohammad Jafar, Salifairus; Malek, Mohd Firdaus; Mahat, Mohd Muzamir; M., Rusop; N. A., Asli (Faculty of Applied Sciences, 2020)
The synthesis of graphene by double thermal chemical vapor deposition (DTCVD) using waste of industrial cooking oil (WICO) as a natural carbon source was investigated. The synthesis parameter (Argon gas flow rate) was varied between 50 sccm to 300 sccm by 50 sccm increments. The function of Argon gas is to provide ambient condition, remove the atmospheric air from the tube and could improve the crystallinity of graphene during synthesis. WICO (from AYAMAS food processing) was placed in the first furnace (precursor furnace) and nickel was placed in the second furnace (deposition furnace). During the synthesis, elevated quantities of carbon from the source material are separated and precipitated on the Nickel surface. The sample were characterized by using Field Emission Scanning Electron Microscopy (FESEM), X-Ray Diffraction (XRD), Energy Dispersive X-ray (EDX), and Ultraviolet Visible (UV-Vis) spectroscopy. Based on FESEM images, at 250 sccm, hexagonal graphene formation was observed. Besides, optical properties can be seen by UV-Vis and as the results show that 250 sccm is the highest reflectivity value. Consequently, graphene synthesis from WICO using various Argon gas flow rate as precursor is successfully demonstrated.